Penentuan Jumlah Tenaga Kerja Guna Meningkatkan Produktifitas pada Bagian Produksi UD. Redline - Hadisaputra, Sasongko Adji; Putri , Erni Puspanantasari (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Redline is a home industry that produces sandals. UD. The current redline must prioritize the efficiency and effectiveness of production operations. A business can be said to be efficient if it is able to produce products based on consumer demand. One of the factors that influences the completion of requests is working time, the personnel involved in completing a production. For example, the aim of this research. This research focuses on the production of men's flip-flops to determine the standard time for each worker and the labor requirements required by UD. Redline for each job. Using the Workload Analysis (WLA) method. After this method was implemented, the research results showed that the process of making 1 unit of product took 12.33 minutes with 8 workers with additional overtime time and a cost of Rp. 120,129,600